Os resíduos sólidos da cadeia do couro sob a ótica do design para a sustentabilidade: um olhar sobre os curtumes - Resende, Geruza de Oliveira (2021)
Leather is the result of the process of tanning the skins of animals slaughtered using vegetable tannins or chromium. Even favoring a great economic advance for Brazil, the leather chain involves processes that generate different types of hazardous waste that, when stored and/or disposed of incorrectly, become a serious threat to the environment. In the country there are sustainability certificates applicable to tanneries as a way of tracking factories in social, economic and environmental terms. In this research, it was proposed to study the contribution of design, in the environmental scope, on the relationships between environmentally sustainable products and determinants of ethical and environmental concepts, to promote cleaner production in the manufacture of leather. This study aimed to identify the critical points of the pre-production of leather in tanneries in relation to environmental aspects and the possibilities of intervention from a design perspective. The methodology used consists of an unsystematic bibliographic review on Brazilian tanneries, industrial waste from the sector, export and production of leather and on design for sustainability. The D4S tool was applied within the scope of ecodesign for a qualitative analysis of the leather life cycle design approach in order to have clarity of information on the pre-production process of the material. The research concludes that the leather sector is complex and relevant for the country, but at all stages of the process there is a lack of data identified in terms of transparency, which is in line with the proposal to have a sustainability seal that performs a biannual screening. Regarding non-certified tanneries, there is no clear data available, as these tanneries represent 86% of Brazilian leather production. Such information is not reached even by the company's own websites. Well, not even companies that are certified offer websites for communicating information; uncertified companies are totally unknown. The work proves to be relevant in validating the importance of communicating data so that one can have a greater control of the whole process of tanning the skin until the stage of sale of the product.